Diversidade microbiana do trato genital feminino - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The role of the human microbiota in health and disease processes has received increased attention due to the ease of characterization of microbial communities using independent culture methods, which are based on the analysis of hypervariable regions of the gene 16S rRNA. The vaginal microbiota is inhabited by microbial communities that play a very important role in the maintenance of vaginal homeostasis and in the presence of colonization by pathogenic microorganisms, but the mechanisms by which they exert this influence are not yet so well defined. in this context, an understanding of their relative abundance and variations is necessary for the recognition of potential pathogenic microorganisms and the physiological processes of protection of this microbiota. This study evaluated the vaginal microbial diversity in four different conditions: I Microbiota Normal II Vaginal Candidosis Microbiota III Bacterial vaginosis microbiota IV microbiota presenting pre-malignant and malignant lesions of the cervix. Cervical samples from 187 women were collected, characterized and diagnosed at the molecular level for the presence of HPV, C. trachomatis, T. vaginalis e N. gonorrhoeae. HPV positive samples were genotyped at ABI 3500 and HPV co-infection were related to the presence of other pathogens and socio-economic and clinical factors obtained through the questionnaire filled out by the volunteers. Significance and association analyzes were performed using the Chi-square Test of Pearson, exact of Fischer’s Test and Kruskal-Wallis test using R 2.9.0. After the groups were composed, four libraries of amplicons of the regions V1-V2 of the gene 16S rRNA and, later sequenced on Ion PGM platform. The sequences generated were analyzed using the QIIME and classified by comparison in the Greengenes database. the prevalence found for HPV was 51.33%, and the most prevalent types were HPV 16, 58 and 33. The prevalence found for CT and TV were 6.42% and 12.83%, respectively, with co- HPV / CT infection in 5.20% and HPV / VT in 6.25% of the women. The DNA of N. gonorrhoeae were not found in samples. as to the estimation of microbial diversity, the number of samples sequenced was enough to guarantee coverage of the total diversity found. Overall abundancy revealed a predominance of the genus lactobacillus on the four study groups, followed by the genres Ureaplasma, Prevotella and Shuttleworthia, followed by the study groups. the greatest microbial diversity was found in the vaginosis group, with the most abundant genera Prevotella, Shuttleworthia and Megasphaera, followed by the lesion group, abundance of genders Ureaplasma, Prevotella e Shuttleworthia. The differences at the species level are extremely necessary for the understanding of the physiological role of the vaginal microbial in the maintenance of autochthonous balance and of pathogenic mechanisms in the development of diseases related to vaginal microbiota. In addition, an understanding of the functionality of the types of CST is necessary to complement what we already know about its structure. Studies are needed to investigate the changes and stability of this microbiota.
Keywords: Diversidade microbiana; Vagina; Gene 16S rRNA; Bactéria; Ion PGM; CIÊNCIAS BIOLÓGICAS: MICROBIOLOGIA